Beliefs about Feedback Provision in EFL Writing and the Actual Practices by an Experienced Indonesian Teacher - Farida, Muthia (English Education:Journal of English Teaching and Research, 2022)
This article reports the research on an experienced Indonesian teacher’s beliefs about feedback provision and her actual practices in an EFL writing classroom. Previous work has conducted analyses of teacher beliefs about feedback, but there is a scarce of research focusing on teacher beliefs and practices on feedback provision to experienced EFL teacher, especially in the Indonesian context. Therefore, this case study investigates an experiencdEFL teacher who taught advanced writing courses in one of the leading universities in Indonesia. The data used were qualitative. In order to gain the data, a preliminary interview, observation, and a retrospective interview were carried out, respectively. Samples of the students’ work were reviewed as a supplementary. The data analysis was done through data transcription, data reading, data data reduction and categorization, data comparison, data description and interpretation, and finally drawing conclusion. The findings show that the teacher believed that feedback was essential and, thus, she put herself as a major source of feedback for her students. Her beliefs influenced her practices to optimize her feedback provision, including her preferences in terms of modes, types, and sources of feedback. Her professional coursework and experiences played important roles in leading consistency between her beliefs and practices. For future teaching practices, it is suggested for teachers to equip themselves with adequate knowledge and skills, and to incorporate various methods to maximize their feedback provision. For future research, it is strongly recommended to use this reflective interview to help capture teacher beliefs behind their actual practices.